THE HERO’S JOURNEY OF MONSTER IN FRANKENSTEIN: OR MODERN PROMETHEUS NOVEL BY MARY SHELLEY - Hajrah, Siti; Arifin, M. Bahri; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACTThis research focuses on the journey of Monster’s character as the hero in Frankenstein: or Modern Prometheus novel by Mary Shelley. The purposes of this research are to present the extent of plot connected to the hero’s journey of Monster and identify how Monster can be depicted as hero by Joseph Campbell theory. Monomyth or Hero’s Journey theory by Joseph Campbell was used as the main theory to find out the stages of hero’s journey in Monster’s character. The method used in this research is a qualitative method. The data source of this research is a novel entitled Frankenstein: or Modern Prometheus by Mary Shelley. The data are words, sentences, paragraphs, narrations and dialogue that contain the description of the plot and hero’s journey.There are two results of this research. Firstly, it is found that the plot pattern in this novel is connected to the hero’s journey theory. Secondly, it showed that the Monster’s character undergoes all the eleven stages which are in line with Campbell’s Monomyth. These eleven stages are, 1. the call to adventure, 2. refusal of the call, 3. supernatural aid, 4. the crossing of the first threshold, 5. the belly of the whale, 6. the road of trials, 7. atonement with the father, 8. apotheosis, 9. the ultimate boon, 10. refusal of the return and 11. freedom to live. Therefore, this research had concluded that the Monster can be depicted as a hero based on his journey that followed the theories of plot and hero’s journey. Key words: Hero’s Journey, Plot, the Monster, Frankenstein or Modern Prometheus. ABSTRAK Penelitian ini berfokus pada karakter monster sebagai pahlawan dalam novel Frankenstein: or Modern Prometheus karya Mary Shelley.Tujuan dari penelitian ini adalah untuk menyajikan sejauh mana plot yang berhubungan dengan perjalanan Monster dan mengidentifikasi bagaimana Monster dapat digambarkan sebagai pahlawan menurut teori Joseph Campbell. Teori Monomyth atau Perjalanan Pahlawan oleh Joseph Campbell digunakan sebagai teori utama untuk mengetahui tahapan perjalanan pahlawan dalam karakter Monster. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Sumber data penelitian ini adalah novel Frankenstein: or Modern Prometheus karya Mary Shelley. Data berupa kata-kata, kalimat, paragraf, narasi dan dialog yang memuat deskripsi plot dan perjalanan pahlawan. . Ada dua hasil dari penelitian ini. Pertama, ditemukan bahwa pola plot dalam novel ini terkait dengan teori perjalanan pahlawan. Kedua, ini menunjukkan bahwa karakter Monster mengalami kesebelas tahap yang sejalan dengan Campbell's Monomyth. Kesebelas tahapan tersebut adalah, 1. the call to adventure, 2. refusal of the call, 3. supernatural aid, 4. the crossing of the first threshold, 5. the belly of the whale, 6. the road of trials, 7. atonement with the father, 8. apotheosis, 9. the ultimate boon, 10. refusal of the return and 11. freedom to live. Oleh karena itu, penelitian ini menyimpulkan bahwa Monster dapat digambarkan sebagai pahlawan berdasarkan perjalanannya yang mengikuti teori plot dan perjalanan pahlawan.Kata Kunci: Perjalanan Pahlawan, Alur, Monster, Frankenstein or Modern Prometheus.